Medical and social characteristics of children with tuberculosis in conditions of social insufficiency in the Irkutsk region - E. Y. Zorkaltseva; S. V. Pugacheva; A. S. Tolstykh (Acta Biomedica Scientifica, 2017)
Background. In cases of tuberculosis in children, contacts with patients with drug-resistant forms are often detected. Treatment and prevention of the disease is based on these data and adherence to treatment. Aims. To analyze the social status of the family of children with tuberculosis, clinical forms and drug resistance of MBT in patients who are sources of infection in the outbreak for adequate planning of preventive treatment of contact and treatment of children with tuberculosis. Materials and methods. The study involved 150 children with tuberculosis treated in a hospital in 2009-2012 and 142 children - in 2015-2017. We studied social factors and drug resistance of Mycobacterium tuberculosis in adult patients - sources to child transmission. Drug resistance of MBT cultures was determined by Löwenstein - Jensen medium and automated system BACTEC MGIT 960. Results. 50.0 % of children with tuberculosis are patients of preschool age, 33.0 % of children aged under 3 years. From 2009-2012 to 2015-2017 the proportion of socially disadvantaged families fell from 68.0 % to 45.1 %. At the same time the proportion of children with tuberculosis, contracted from a known contact decreased from 70.0 % to 57.0 %. Often children get infected from mother or from several close relatives (mother, father, grandfather, grandmother), TB patients source of infection of children are often diagnosed with infiltrative (21.9-38.3 %) and fibro-cavernous tuberculosis (17.0-21.0 %). To 2015-2017 multi-drug resistance in the nidi was recorded at 52.2 %. The development of tuberculosis in children was facilitated by the defects of preventative measures: absence of BCG vaccination (from 9.0 to 14.0 % of children), the absence of preventive treatment (55.3-67.5 %).